PENGAWASAN LALU LINTAS HEWAN, PANGAN ASAL HEWAN DAN PRODUK PERTERNAKAN PADA POS LINTAS BATAS - Irma Wahyuni E.21108041 (FISIP Universitas Tanjungpura, 2014)
The problem of animals traffics / livestock , based food from animal and farm products on Transboundary Monitoring Post in the Entikong, the province of West Kalimantan was increased , the illegal food from animal origin / livestock phenomenon and product of livestock easily found in markets and supermarkets . The purpose of this research has to know and analyze the traffic control of based food from animal/ livestock and the products of livestocks doing by the Department of Animal Husbandry and Animal Health West Kalimantan province on Transboundary Monitoring Pos in Entikong . This research method is descriptive research that is describe the object to explore the facts and the data will describe real situation or real event . The technique of data analysis is qualitative analysis , with data reduction and sort of the data . The results of this research is showed responsibilities and authority from the officers to animal/livestock illegal trafficking and the products are not optimal , not suitable handling with the procedure and not effective the control and coordination among the institute. The conclusion of this research is the research showed in implementation of traffic control animals, based food from animal, and farm products on Transboundary Monitoring Post in the Entikong, the province of West Kalimantan is not effective. Because of that researcher suggested that the Department of Animal Husbandry and Animal Health West Kalimantan Province to provide and improve the human resource, in quality and quantity, positiom the expert officers in theTransboundary Monitoring Post, Entikong to control the circulation of animals / livestock so the products can implemented optimally . Key Words : Animals/livestock, Descriptive,Transboundary Monitoring Post